Photochemical [2 + 2] cycloaddition reactions of 6-alkenyl-3-phenylcyclohex-2-en-1-ones: using biradical conformation control to account for exceptions to the "rule of five" - DRAPER, SYLVIA MARY (My University, 2011)
A series of 6-alkenyl-3-phenylcyclohex-2-enones has been synthesised and the structures of the products obtained from them on irradiation have been determined. The 6-propenyl compounds afforded a tricyclic `parallel? [2 + 2] cycloaddition product and a bicyclic enone resulting from hydrogen abstraction in the biradical intermediate. The 6-butenyl and 6-pentenyl analogues gave `crossed? cycloaddition products only. Although the regiochemistry of these cycloaddition reactions cannot be explained in terms of the `rule of five?, it is compatible with the concept of `biradical conformation control? which is based on a consideration of the energy and structure of the possible 1,4-biradical intermediates.
PUBLISHED
Keywords: Chemistry